Distribution, abundance and length of macrozooplankton species in Svalbard fjords - Lunde, Andreas (Helsingin yliopisto, 2023)
Macrozooplankton is an understudied size class of plankton in the Arctic, but even though species composition is similar around the Svalbard archipelago, the relative composition can act as a proxy for climate change. This study investigated if the fjords around Svalbard are similar in species composition and if any differences could be explained. 11 fjords were sampled with a focus on common and indicator species in terms of abundance, relative composition and length distribution. I found low presence of T.libellula and high abundances of T.abyssorum and T.inermis. T.abyssorum was the only species whos abundance was significantly correlated to water mass (Atlantic water), but T.libellula, T.abyssorum, T.inermis, T.longicaudata and A.digitale all showed significant differences in length distribution. This study provides further understanding of species composition in the different high Arctic fjords around Svalbard.